2023
DOI: 10.1021/acs.inorgchem.3c02808
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of Mesoporous M2P2O7 (M = Mn(II), Co(II), and Ni(II)) and M2–xCoxP2O7 and Transformation to Their Metal Hydroxides with Decent Charge Capacity in Alkali Media

Işıl Ulu,
Burak Ulgut,
Ömer Dag

Abstract: A general synthetic method has been developed to synthesize spherical mesoporous metal pyrophosphate (m-M 2 P 2 O 7 ) particles and to fabricate graphite rodcoated (GR-M 2 P 2 O 7 ) electrodes, which are important as energy storage materials. The clear aqueous solution of the ingredients (namely, [M(H 2 O) 6 ](NO 3 ) 2 , H 4 P 2 O 7 , water, and P123) assembles, upon excess water evaporation, into a mesostructured M 2 H x P 2 O 7 (NO 3 ) x •nH 2 O−P123 semisolid that is calcined to produce the spherical m-M 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…We previously showed that the graphite rod is a better substrate for the fabrication of mesoporous CaFe 2 O 4 and M 2 P 2 O 7 (fabricated using the MASA method); the mesoporous CaFe 2 O 4 and M 2 P 2 O 7 electrodes undergo mechanical degradation in an alkaline media over the FTO surface, but the same electrodes that are fabricated over the graphite surface are robust and unaffected during the electrochemical test. 39,44,45 However, this is not the case in the m -LMO electrodes, which undergo disproportionation reactions and display a similar degradation over both substrates. The only advantage of using a graphite substrate might be a smaller IR-drop in the OER potentials and better overpotential values.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We previously showed that the graphite rod is a better substrate for the fabrication of mesoporous CaFe 2 O 4 and M 2 P 2 O 7 (fabricated using the MASA method); the mesoporous CaFe 2 O 4 and M 2 P 2 O 7 electrodes undergo mechanical degradation in an alkaline media over the FTO surface, but the same electrodes that are fabricated over the graphite surface are robust and unaffected during the electrochemical test. 39,44,45 However, this is not the case in the m -LMO electrodes, which undergo disproportionation reactions and display a similar degradation over both substrates. The only advantage of using a graphite substrate might be a smaller IR-drop in the OER potentials and better overpotential values.…”
Section: Resultsmentioning
confidence: 97%
“…S28‡) undergo a chemical transformation into layered β-M(OH) 2 in alkaline media. 44,45 The characterization and transformation processes of Mn 2 P 2 O 7 have been extensively investigated in our previous publication. 45 Therefore, we will focus on the disproportionation reaction on the graphite rod-coated mesoporous Mn 2 P 2 O 7 electrode, which is already transformed into β-Mn(OH) 2 before any electrochemical tests upon dipping the electrode into a 3.0 M KOH electrolyte solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the catalyst exhibited only good ORR activity. It is therefore postulated that the phosphating of the active center may endow the catalyst with bifunctionality. The potential center of cobalt pyrophosphate (Co 2 P 2 O 7 ) allows for the maintenance of several intermediate states of cobalt geometry, including tetrahedral, trigonal bipyramidal, and low-octahedral configurations . In addition, the flexibility between the PO 4 3– groups and Co promotes the flexible coordination of PO 4 3– groups with transition metals, which can easily change their local positions to ensure effective redox changes of the transition metals .…”
Section: Introductionmentioning
confidence: 99%